Electrolyte Chemistry Enables Simultaneous Stabilization of Potassium Metal and Alloying Anode for Potassium‐Ion Batteries. (26th September 2019) - Wang, Hua; Yu, Dandan; Wang, Xiao; Niu, Zhiqiang; Chen, Mengxue; Cheng, Liwei; Zhou, Wei; Guo, Lin
Abstract: Alloying anodes are promising high‐capacity electrode materials for K‐ion batteries (KIBs). However, KIBs based on alloying anodes suffer from rapid capacity decay due to the instability of K metal and large volume expansion of alloying anodes. Herein, the effects of salts and solvents on the cycling stability of KIBs based on a typical alloying anode such as amorphous red phosphorus (RP) are investigated, and the potassium bis(fluorosulfonyl)imide (KFSI) salt‐based carbonate electrolyte is versatile to achieve simultaneous stabilization of K metal and RP electrodes for highly stable KIBs. This salt‐solvent complex with a moderate solvation energy can alleviate side reactions between K metal and the electrolyte and facilitate K + ion diffusion/desolvation. Moreover, robust SEI layers that form on K metal and RP electrodes can suppress K dendrite growth and resist RP volume change. This strategy of electrolyte regulation can be applicable to other alloying anodes for high‐performance KIBs. Abstract : Das Salz in der Suppe : Durch Zersetzung von hochaktivem K‐Metall und großen Volumenänderungen zeigen Legierungsanoden üblicherweise schlechte Leistungen in Speicherzyklen von K‐Ionen. Hier wird gezeigt, dass die Regulation der Elektrolytchemie einen möglichen Ansatz darstellt, um K‐Metall und Legierungsanoden zu stabilisieren und dadurch die Entwicklung von effizienten K‐Ionen‐Batterien basierend auf Legierungsanoden zu ermöglichen.